IMPLEMENTATION OF THE PROJECT-BASED APPROACH IN THE ACTIVITIES OF LOCAL SELF-GOVERNMENT BODIES FOR JUVENILE DELINQUENCY PREVENTION - Velychko, Larysa; Orel, Yurii (Public Management and Policy, 2025)
The article substantiates the expediency of systemic implementation of the project-based approach in the activities of local self-government bodies (LSGBs) of Ukraine to increase the effectiveness of juvenile delinquency prevention. The urgency of the problem is exacerbated by the full-scale war in Ukraine and the socio-economic crisis. Traditional prevention methods are ineffective under these conditions. The purpose of this article is the scientific substantiation and practical modeling of the systemic introduction of project management into the activities of local self-government bodies for juvenile delinquency prevention. The project-based approach, unlike the functional one, ensures purposefulness, resource planning, risk management, and a results-oriented focus. Analysis of international experience (USA, EU) confirms the effectiveness of projects in this area, while Ukraine experiences fragmentation and weak coordination of stakeholder activities. It is proposed to use P. Ebkom’s "5 I’s" model (Intelligence, Intervention, Implementation, Involvement, and Impact) for developing preventive projects. Key barriers to implementing the project-based approach in LSGB activities concerning juvenile delinquency prevention have been identified: low project maturity of LSGBs, resource deficit, organizational resistance, and lack of systemic monitoring. Recommendations include establishing project offices/coordinators in LSGBs, systemic training for specialists, fostering interdepartmental cooperation through project teams, implementing SMART indicators, and actively attracting external funding. The necessity of a comprehensive approach by LSGB leadership to project management as a strategic reform is emphasized. It has been determined that implementing the project-based approach will increase the effectiveness of prevention, contribute to reducing juvenile delinquency, and promote the sustainable development of community’s mechanism for implementing a national financial education strategy in Ukraine.